2009
DOI: 10.3141/2140-05
|View full text |Cite
|
Sign up to set email alerts
|

Automated Analysis of Pedestrian–Vehicle Conflicts Using Video Data

Abstract: Pedestrians are vulnerable road users, and despite their limited representation in traffic events, pedestrian-involved injuries and fatalities are overrepresented in traffic collisions. However, little is known about pedestrian exposure to the risk of collision, especially when compared with the amount of knowledge available for motorized traffic. More data and analysis are therefore required to understand the processes that involve pedestrians in collisions. Collision statistics alone are inadequate for the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
91
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 169 publications
(93 citation statements)
references
References 19 publications
0
91
0
1
Order By: Relevance
“…However, some examples of work on conflicts between vehicles and other road users can be found in the literature, mostly for the purpose of assessing the safety of pedestrian crossings and the interactions within mixed traffic flows. These include: (24), where a method categorising vehicle-pedestrian conflicts at crossings into one of 13 types was derived with a view of identifying potential safety hazards; (25), where pedestrianvehicle conflicts along with traffic characteristics data were used to perform automated assessment of the safety of Pelican crossings in the UK; and (26)(27), in which an automated video analysis system to classify road users as vehicles or pedestrians, identify conflict situations between them and categorise them according to their severity was developed. Also, there are several instances of methods adapted from well-established vehicle-vehicle methods to monitor pedestrian-vehicle conflicts, such as: the application of the STCT in (28) and (29); the use of the USDoTCT in (30); and the adaptation of the CIHTCT in (12) and in (31).…”
Section: Introductionmentioning
confidence: 99%
“…However, some examples of work on conflicts between vehicles and other road users can be found in the literature, mostly for the purpose of assessing the safety of pedestrian crossings and the interactions within mixed traffic flows. These include: (24), where a method categorising vehicle-pedestrian conflicts at crossings into one of 13 types was derived with a view of identifying potential safety hazards; (25), where pedestrianvehicle conflicts along with traffic characteristics data were used to perform automated assessment of the safety of Pelican crossings in the UK; and (26)(27), in which an automated video analysis system to classify road users as vehicles or pedestrians, identify conflict situations between them and categorise them according to their severity was developed. Also, there are several instances of methods adapted from well-established vehicle-vehicle methods to monitor pedestrian-vehicle conflicts, such as: the application of the STCT in (28) and (29); the use of the USDoTCT in (30); and the adaptation of the CIHTCT in (12) and in (31).…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of traffic conflicts and the measurement of conflicts indicators have often been conducted through manual observations. Recent work addressed the opportunity for the automation of traffic-conflicts data collection (Saunier & Sayed, 2007) and provided a guideline for the objective measurements of conflicts indicators (Ismail et al, 2009;Laureshyn et al, 2009;Sayed et al, 2012). Large-scale application validation of this line of research was demonstrated in Autey et al (2012) and Ismail et al (2010)).…”
Section: Conflicts Analysismentioning
confidence: 98%
“…The automated approach solves many shortcomings in manual data collection and provides a more practical and efficient way to capture, store, and analyze elements of the traffic information for largescale data. Automated video analysis was used before in extracting conflict data in Ismail et al, 2009;Sayed et al, 2013) and the detection of violations in (Ismail et al, 2011;Zaki et al, 2012). Automated video data analysis for traffic movements is a practical computer vision application, where road users are detected and their travel trajectories tracked in an automated manner.…”
Section: Introductionmentioning
confidence: 99%
“…No processo de coleta de dados, em travessias nos acessos a rotatórias, o autor identificou limitações que tornam necessário rastrear manualmente alguns objetos. Recentemente, Ismail et al (2009) desenvolveram uma ferramenta automática para rastrear pedestres e veículos e detectar eventos que possam conduzir a colisões, calculando indicadores de severidade dos conflitos. Os autores destacam que para utilizar a ferramenta em ambientes com fluxos maiores, no entanto, são necessários aperfeiçoamentos.…”
Section: Processos De Coleta De Dadosunclassified